The financial impact of SBRT for oligometastatic disease: A population-level analysis in Belgium. (April 2020) - Nevens, Daan; Kindts, Isabelle; Defourny, Noémie; Boesmans, Leen; Van Damme, Nancy; Engels, Hilde; Van de Voorde, Carine; Lievens, Yolande
Highlights: We observe a large increase in the number of oligometastatic patients treated with SBRT in Belgium. Three growth scenarios and the provider and payer costs were combined to estimate the impact on the radiotherapy budget at population level, showing large variations. Further real-life clinical and financial monitoring and prospective data gathering is necessary. Abstract: Introduction: There is a steady rise in Stereotactic Body RadioTherapy (SBRT) utilization in oligometastatic disease (OMD). This may generate important financial consequences for radiotherapy budgets. The National Institute for Health and Disability Insurance of Belgium (NIHDI) initiated a coverage with evidence development (CED) project for innovative radiotherapy, including SBRT, in 2011. A cost calculation and budget estimation for SBRT in the OMD setting was carried out. Materials and methods: Predictive growth scenarios for future uptake of SBRT for OMD in Belgium were developed using demographics and CED data. The provider cost of SBRT for OMD in Belgium was calculated using the Time-Driven Activity-Based Costing (TD-ABC) model developed by ESTRO-HERO, alimented with national data on resources, treatments and operational parameters, and compared to the new reimbursement. Combining these, the future financial impact of this novel treatment indication for healthcare providers and payers in Belgium was evaluated. Results: The number of 428 OMDs treated with SBRT in Belgium in 2017 is expected to increase between 484 and 2073 courses annually by 2025. A provider cost of €4360 per SBRT was calculated (range: €3488–€5654), whereas the reimbursement covers between €4139 and €4654. Large variations in potential extra provider costs by 2025 ensue from the different scenarios, ranging between €1, 765, 993 and €9, 038, 754. Provider costs and reimbursement show good agreement. Conclusion: Although the financial impact of SBRT for OMD in Belgium is forecasted to remain acceptable, even in extreme scenarios, further clinical trials and real-life clinical and financial monitoring with prospective data gathering are necessary to refine the data.